Faktor-Faktor yang Berhubungan dengan Kelelahan Kerja pada Pekerja Konveksi Bagian Penjahitan di CV. Aneka Garment Gunungpati Semarang - Atiqoh, Januar; Wahyuni, Ida; Lestantyo, Daru (Jurnal Kesehatan Masyarakat (Undip), 2014)
Fatigue can be influenced by several factors that can come from within the individual as well as of the work environment. CV. Aneka Garment Gunungpati Semarang is informal industry convection with all the sewing workers are women. The purpose of this research is to analyze the related factors of fatigue on sewing workers at CV. Aneka Garment Gunungpati Semarang. This research is explanatory research using cross sectional study design, where population numbers to the workers is 31 people. Sampling method using total sampling. Data analysis using Chi-Square test for normal distribution of data and Rank-Spearman for data not normally distributed. The results showed that most of respondents heavy work fatigue (71%), most of the old ³40 years (71%), the majority of respondents work >10 years (71%), nutritional status of most respondents in the normal category (50.1%), the posture of most respondents work at level 3 (42.1%), and most of the workload between 30 to <60% (42.1%), it means need repairation for workload. Results of statistical tests showed had relationship between age and fatigue (p = 0.0001), there is a relationship between the during work with fatigue (p = 0.0001), there is no relationship between nutritional status with fatigue (p = 0.191), there is a relationship between working posture with fatigue (p = 0.0001), and there is a relationship between the workload with fatigue (p = 0.0001). Business owners should provide additional lighting in accordance with the type of work (lighting meets 1000 Lux) and doing engineering work station (chair) to fit the body size of workers